Green Prophetic Leadership and Employee Green Performance in the Halal Industry: A Grounded Theory - Rahmat, Taufiq; Ahman, Eeng; W. Mahri, A. Jajang; Setiawan, Yana (Business Innovation Management and Entrepreneurship Journal, 2026)
The halal industry in Indonesia faces a dual imperative: meeting Islamic ethical standards while addressing growing environmental sustainability demands. Despite extensive quantitative research linking Green Human Resource Management (GHRM), Green Knowledge Sharing (GKS), and Organizational Citizenship Behavior for the Environment (OCBE) to Employee Green Performance (EGP), the social processes underlying EGP formation in values-based Islamic organizations remain theoretically underdeveloped. This paper proposes a conceptual framework grounded in Grounded Theory methodology to theorize how EGP is constructed through the interplay of GHRM, GKS, and OCBE, moderated by Green Prophetic Leadership (GPL) in the halal industry of West Java, Indonesia. Drawing on Resource-Based View (RBV) and Social Exchange Theory (SET) as sensitizing concepts, we develop five theoretical propositions and a substantive model organized around the core category of prophetically-anchored green identity construction. This framework contributes to the emerging discourse on Islamic organizational behavior and green management, offering context-sensitive theoretical alternatives to variance-based models dominant in current sustainability management research.